Discussion of 'Metamorphic P - T and retrograde path of high-pressure Barrovian metamorphic zones near Cairn Leuchan, Caledonian orogen, Scotland' - Aoki, K.; Maruyama, S.; Oliver, G.; Omori, S.; Viete, D.; Wilde, Simon; Windley, B. (Cambridge University Press, 2014)
K. Aoki, B. F. Windley, S. Maruyama & S. Omori reply: First, we thank Viete, Oliver & Wilde for their interesting and thought-provoking comments on the timing of the high-pressure granulite facies (HGR) metamorphism recorded in metamorphic rocks at Cairn Leuchan, Scotland, published by Aoki et al. (2013). Based on new metamorphic data of garnetites and garnet-amphibolites at Cairn Leuchan and new zircon U-Pb ages of amphibolitized eclogite at Tomatin, we suggested in our publication that the HGR metamorphism was retrograde after eclogite facies before the c. 470 Ma 'Barrovian metamorphism'. Viete, Oliver & Wilde however speculate that the HGR metamorphism at Cairn Leuchan may have occurred at c. 1000 Ma, as a result of their new U-Pb zircon age of the Cowhythe Gneiss at Portsoy and from previous studies of the geological structure and geochronology. We are grateful for this opportunity to describe, albeit in a preliminary manner, our new understanding and tectonic model of the Caledonian orogen in Scotland and western Ireland of which the Barrovian metamorphism is a key component. A reply to a comment is not the correct place to propose an entirely new paradigm for such a classic orogen, but we will present our model more fully in a future publication.. Copyright © Cambridge University Press 2014.